PENGALAMAN KOMUNIKASI JURNALIS DALAM MELIPUT KASUS KEKERASAN SEKSUAL (Studi Fenomenologi Komunikasi Jurnalis Gorontalo Dalam Meliput Kasus Kekerasan Seksual) - kiraman, novita; Sumarjo; Ramansyah (JAMBURA JURNAL ILMU KOMUNIKASI, 2025)
This study explores journalists’ communication experiences in covering sexual violence cases in Gorontalo. The research was motivated by the complex interactions that arise during the reporting process, encompassing interpersonal, intrapersonal, and mass communication dimensions. The study aimed to describe how journalists in Gorontalo experience, perceive, and manage interactions when reporting on this sensitive issue. A qualitative approach using descriptive phenomenology was employed, involving observation and in-depth interviews with six journalists selected through purposive sampling. The findings reveal that journalists face professional, ethical, and emotional challenges, especially when dealing with child victims. In practice, journalists adopt empathetic and cautious approaches to protect victims' privacy and build trust. External pressures, such as from the police or victims' families, also influence the reporting process. The study concludes that journalists’ experiences in covering sexual violence in Gorontalo involve complex ethical, emotional, and professional challenges, demanding empathy, caution, and social responsibility in communication. These findings highlight the need for training programs for journalists focused on empathetic communication, journalistic ethics, and emotional pressure management. Media outlets must also establish victim-centered reporting guidelines, thus, journalists are not only conveyors of information but also agents of social change who uphold victims’ dignity and raise public awareness.